2010
DOI: 10.1523/jneurosci.1401-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Defined Inhibitory Neurons in the Mouse Spinal Cord Dorsal Horn: A Possible Source of Rhythmic Inhibition of Motoneurons during Fictive Locomotion

Abstract: To ensure alternation of flexor and extensor muscles during locomotion, the spinal locomotor network provides rhythmic inhibition to motoneurons. The source of this inhibition in mammals is incompletely defined. We have identified a population of GABAergic interneurons located in medial laminae V/VI that express green fluorescent protein (GFP) in glutamic acid decarboxylase-65::GFP transgenic mice. Immunohistochemical studies revealed GFPϩ terminals in apposition to motoneuronal somata, neurons in Clarke's col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 64 publications
5
48
1
1
Order By: Relevance
“…4A). The expression of c-fos, an activity-dependent immediate early gene, has previously been used to determine whether neurons are activated in locomotion (Dai et al, 2005;Wilson et al, 2005;Dai and Jordan, 2010a,b;Wilson et al, 2010). The proportion of fluorescent proteinpositive neurons in the GRN expressing Fos increased significantly following a locomotor task (Fig.…”
Section: Lhx3 and Chx10 Neurons Are Activated During Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…4A). The expression of c-fos, an activity-dependent immediate early gene, has previously been used to determine whether neurons are activated in locomotion (Dai et al, 2005;Wilson et al, 2005;Dai and Jordan, 2010a,b;Wilson et al, 2010). The proportion of fluorescent proteinpositive neurons in the GRN expressing Fos increased significantly following a locomotor task (Fig.…”
Section: Lhx3 and Chx10 Neurons Are Activated During Locomotionmentioning
confidence: 99%
“…During spinal cord development, cells from the p2 progenitor domain express a combination of transcription factors, including Lhx3 (Zhou et al, 2000;Karunaratne et al, 2002;Li et al, 2005). These Lhx3ϩ V2 cells diversify into several distinct interneuronal populations: Chx10-expressing glutamatergic V2a and Gata2/3-expressing GABA/glycinergic V2b-c interneurons ( , 2008).…”
Section: Brainstem Versus Spinal Cord Lhx3 and Chx10 Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that many interneurons are rhythmic is also relevant for interpreting the increasing number of studies reporting genetically identified cell types that have locomotor-related activity (Butt and Kiehn 2003;Butt et al 2005;Dougherty and Kiehn 2010;Hinckley et al 2005;Wilson et al 2005Wilson et al , 2010Zagoraiou et al 2009;Zhong et al 2010). Because rhythmic activity is not unique to a few cell types, it is more insightful to compare the relative phases of the locomotor-related activity of the different cell types, which is possible with large-scale imaging and coherence analysis.…”
Section: Implications For the Mouse Hindlimb Locomotor Circuitmentioning
confidence: 99%
“…For example, in the spinal cord, there are several identified interneuron types that have been shown to fire at specific phases of the locomotor cycle. Some interneuron types fire preferentially in the ipsilateral motor output phase, such as those identified by expression of the EphA4 receptor (Butt et al 2005) or the transcription factor Hb9 (Hinckley et al 2005), by cholinergic innervations to motoneurons (Zagoraiou et al 2009), and GABAergic interneurons in the dorsal horn (Wilson et al 2010). Other cell types prefer the contralateral phase, such as Renshaw cells (Nishimaru et al 2006), or can fire in either ipsilateral or contralateral phases, such as subclasses of commissural interneurons (Butt and Kiehn 2003) and V2a interneurons expressing the transcription factor Chx10 (Dougherty and Kiehn 2010;Zhong et al 2010).…”
Section: Introductionmentioning
confidence: 99%